Click Here to Print a Maker Movement Supply Chain: How Invention and Entrepreneurship Will Disrupt Supply Chain Design. Issue 2 (June 2014) - Waller, Matthew A.; Fawcett, Stanley E.
<x xml:space="preserve">Abstract</x> Emerging technologies such as 3D printing promise to transform supply chain design and management. As these new technologies enable inventors to become entrepreneurs, new product introduction cycle times are being reduced and the variety of new products that are introduced through short channels of distribution is increasing. We show that these disruptive forces are growing and may have significant implications for practice, research, and teaching in supply chain management. We identify and elaborate important research questions, calling for theory‐driven research to explain and predict how these phenomena will impact supply chain management.